KELOMPOK PENYELENGGARA PEMUNGUTAN SUARA (KPPS) PEMILU 2019: TANGGUNGJAWAB DAN BEBAN KERJA - Andreas Pandiangan (Department of Social Science, Faculty of Social Science &Law, Universitas Negeri Surabaya, 2019)
The Voting Organizing Group (KPPS) is the spearhead of voting and counting in the 2019 Election. This includes serving the voting rights of the community an election partisicipants.This study aims to explain the responsibilities and burdens of KPPS in the 2019 Election after describing the KPPS journey so far. Within the framework of qualitative policy studies, this study will analyze the regulations of the EMB as well as the responsibilities and duties of KPPS. This study found that the work of KPPS will greatly determine the quality of the 2019 Election and have the opportunity to be sued by the public and participants of the 2019 Election if the implementation of elections does not fulfill the principles: independent, honest, fair, legal certainty, orderly, open, proportional, professional, accountable, effective and efficient. The tasks, authorities anf obligations of such a wide and severe KPPS in the 2019 Election would be offset by changes in organization and facilities and welfare received by the Chair anf Members of the Voting Organizing Group (KPPS).